The idea of the brain : the past and future of neuroscience - Cobb, Matthew (Profile Books, 2021)
"In The Idea of the Brain, renowned scientist Matthew Cobb describes the insights and dead-ends that have marked our quest to understand the brain and offers a view of what the future of neuroscience might hold. Cobb shows how the development of new technologies has informed how we think about the brain--and how we ask questions and design experiments to answer those questions"--